Formulation and evaluation of antifungal gel for tinea corporis by using Achyranthes aspera leaves extract - Gnanakarunyan, T.J.; Christina, T.; Lukirtha, S.; Tharshika, K.; Sivasinthujah, S. (FAHS, USJ, 2025)
The seeds of Trigonella foenum-graecum, commonly known as fenugreek, have been used in various medicinal systems due to their diverse pharmacological properties, including antioxidant, antidiabetic and anticancer activities. This study aimed to evaluate the in vitro antioxidant and alpha-amylase inhibitory activities of methanolic extracts of seeds and sprouts (Day 1, Day 3, and Day 5) of T. foenum-graecum. Seeds and sprouts were dried, powdered, and macerated in methanol to obtain the methanolic extract. The antioxidant activity was assessed using the 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging assay and phosphomolybdenum method using ascorbic acid as standard. The antidiabetic potential was evaluated by the alpha-amylase inhibitory assay using acarbose as standard. Qualitative phytochemical screening was performed on the crude methanol extracts. DPPH assay revealed the lowest half maximal inhibitory concentration (IC50) for Day 3 sprout extract (22.67 μg/ml) whereas the IC50 of ascorbic acid was 12.4 μg/ml, indicating the highest antioxidant capacity. In the phosphomolybdenum method, the Day 3 sprout extract exhibited the highest antioxidant activity, followed by Day 1, dry seeds, and Day 5 sprouts extracts. Regarding alpha-amylase inhibition, the dry seed extract exhibited the highest inhibitory activity (IC50 = 104.56 μg/ml), whereas IC50 of acarbose was 829.03 μg/ml, followed by Day 1 and Day 3 sprout extracts. The qualitative phytochemical analysis confirmed the presence of alkaloids, flavonoids, saponins, tannins, gum, mucilage, sterols, glycosides, and phenolic compounds in the extracts. The Day 3 sprout extract exhibited the highest antioxidant activity, while the dry seed extract showed the highest alpha-amylase inhibition. The findings suggest that T. foenum-graecum sprouts, particularly on Day 3, could be beneficial in managing diabetes and its complications. Further, methanol extract of T. foenum-graecum could be used to identify the specific antidiabetic compounds with antioxidant activity, providing further insight into their therapeutic potential.